Pancasila sebagai landasan filosofis dalam penegakan hak asasi manusia di indonesia - Irzam Fabiansyah, Achmad Khafid (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the foundation of the Indonesian state, plays a central role in providing a philosophical and moral foundation for the enforcement of Human Rights (HAM). The basic values ​​contained in the five principles of Pancasila include fundamental rights such as religious freedom, social justice, unity, and the right to participate in national and state life. Pancasila serves as a bridge between local values ​​and internationally recognized universal principles of human rights, and emphasizes that the enforcement of human rights must consider the social, cultural, and diversity aspects of the Indonesian nation. The characteristics of human rights in Indonesia, which are rooted in the values ​​of Pancasila, emphasize the balance between individual freedom and social responsibility, inclusiveness in diversity, and fair legal protection. Although still faced with various challenges in the implementation of human rights, strengthening the values ​​of Pancasila as a moral and legal foundation is believed to enrich and strengthen the achievement of sustainable justice and national unity. The application of Pancasila values ​​in the context of human rights is key to creating a democratic, just, and dignified Indonesian society.